Financial Inclusion: A Veritable Tool For Inclusive Growth And Poverty Alleviation In Nigeria - Uwakaeme, O. S. (Archives of Business Research, 2018)
In recent times, inclusive growth has become a national policy objective worldwide. In the context of Nigeria’s growth planning, it is a relatively new terminology which got the attention of policy makers in October 2012.Inclusive growth has the literal meaning of the two words that refers to both the pace and the pattern of the economic growth. It basically means, broad based, shared, and pro-poor growth. In Nigeria, the formal financial system provides services to about 35% of the economically active population while the remaining 65% are excluded from access to financial services. These 65% are often served by the informal financial sector some of which are not regulated. The non-regulation of the activities of the informal sector has serious implications for the Central Bank of Nigeria’s ability to exercise its mandate of promoting monetary stability and sound financial system .Economic growth and development in any economy is propelled by the quality of goods and services provided within that economy as well as their competiveness with other economies. One of the major factors that have constrained the pace of economic growth and development is lack of access to sustainable financial services by a greater proportion of the populace. Inclusive growth will follow at a faster pace when every segment of the populace engages in the productive process through access to sustainable financial services. Access to financial services could assist to alleviate poverty and promote both growth and standard of living when the economic active-poor and the disadvantaged are enabled to save, borrow and reinvest for the growth of the real sector of the economy. In this, paper an effort has been made to understand the inclusive growth phenomenon, its need and sustainable financial inclusion as a veritable tool to attain it, relative to Nigerian experience.